Vasculogenic mimicry and p53 expression in esophageal squamous cell carcinoma patients of Kazakh ethnicity, the association between vasculogenic mimicry and p53 expression and its influence on prognosis - Buhulula, Luyeye Sostenes; Ainiwaer, Julaiti; Liwei, Zhang; Sheyhidin, Ilyar; Shutao, Zheng; Niyaz, Madiniyet (International Surgery Journal, 2025)
Background: Esophageal cancer (EC), particularly esophageal squamous cell carcinoma (ESCC), is prevalent in Xinjiang, with poor prognosis and notable ethnic differences. Kazakhs are the most affected group. The p53 gene mutation is linked to tumor malignancy and metastasis in EC, though its prognostic role is debated. Vasculogenic mimicry (VM), a non-classical angiogenesis model, contributes to tumor progression and correlates with poor outcomes. This study investigates the relationship between VM and p53 expression in Kazakh ESCC patients to understand their clinical and prognostic significance. Methods: This retrospective cross-sectional study analyzed 76 Kazakh ESCC patients to assess VM and p53 expression using histological staining and immunohistochemistry between December 2010 and November 2015. Clinicopathological features, survival outcomes, and the correlation between VM and p53 were evaluated using Spearman correlation, Kaplan-Meier curves, and Cox regression analysis. Ethical approval and informed consent were obtained. Results: VM was identified in 42.1% of Kazakh ESCC tissues, associated with advanced stages, lymph node metastasis, and poor differentiation (p<0.001). Kaplan-Meier analysis revealed that VM presence significantly reduced survival time (p<0.05). Mutant p53 expression correlated with tumor differentiation but not survival. Spearman analysis showed a significant association between VM and p53 positivity. VM and lymph node metastasis were independent prognostic factors, underscoring VM’s critical role in ESCC progression. Conclusion: Vasculogenic mimicry (VM) is a marker of poor prognosis in Kazakh EC, correlating with advanced stages and higher metastasis rates. The association between VM and p53 mutations highlights their combined role in tumor progression and potential as therapeutic targets.